The Impact of the English Language on Italian Lexis A study on students from the University of Catania in international exchanges - Tutino, Vincenza; Littunen, Heidi (European Scientific Journal, ESJ, 2022)
This research paper aims to explore how learning English in multilingual contexts motivates and influences the use of English terms in Italian lexis by Italian university students. The topic of this study is valuable because it focuses in detail on the impact of English as a second language during the international exchange programmes. University students’ international exchange has developed a lot in the last decades, having a positive influence on their personal growth and linguistic skills, especially from the English language proficiency point of view. The impact of English learning on the mother tongue lexis has been analyzed. The data collection instrument was a questionnaire. The results were received directly through Google Module and consequently analyzed. The sample group was made up of the students of the departments of Political and Social Sciences, Educational Sciences and Humanities and Languages of the University of Catania. Furthermore, learning of the second language has been inspected questioning how the exposition to multilingual contexts can determine an impoverishment of the respondents’ Italian vocabulary or otherwise an enrichment process towards a lingua franca that would help a better communication with young people of other countries. The hypothesis that the English language is a lingua franca and it has enriched the mother tongue lexis was widely confirmed and we can sum up, through the survey results, that the sample of students is well aware of the influence that the English language has on their communication in native language.